UPAYA GURU DALAM MENINGKATKAN KEMAMPUAN GERAK LOKOMOTOR MELALUI PERMAINAN TRADISIONAL BOI-BOIAN PADA KELOMPOK B DI TK ISLAM RUMAH ILMU CIMAHI - Sahanah Sahanah; Ema Aprianti (IKIP Siliwangi, 2018)
The study was conducted based on the findings of the problem that tekait with rough motor skills in group B in Islamic Kindergarten of Rumah Ilmu Cimahi. Problems that exist in the Islamic Kindergarten House Science is almost no land to play, where the physical movement of children requires a wide range of movement. Also habituation of children who prefer to watch television and play dadget. Traditional boi-boian games can support rough motor stimulation in children. The boi-boian game activities conducted in this research succeeded in assisting one of these obstacles. In the process performed can be seen that children who had a poor motor skills are less good, began to do some rough motor activities better. Based on the background of the above research shows the need for efforts in improving the abilities of rough motor physical children. The formulation of the problem in this research is